Acupuncture for patients with premature ovarian insufficiency: A systematic review protocol - Huang, Li (Medicine (Baltimore), 2019)
BACKGROUND: Premature ovarian insufficiency (POI) is a difficult-to-treat gynecological disorder with complex etiologies. Although acupuncture has gained increased popularity for the management of POI, evidence regarding its efficacy is lacking. This systematic review protocol aims to describe a meta-analysis to assess the effectiveness and safety of acupuncture for patients with POI. METHODS: The following 10 databases will be searched from the publishment to July 2019: PubMed, Embase, the Web of Science, the Cochrane Central Register of Controlled Trials, 4 Chinese databases (China National Knowledge Infrastructure, Wanfang Digital Periodicals, Chinese Biomedical Literature Database, Chinese Scientific Journal Database database), 1 Korean medical database (KoreaMed), 1 Japanese medical database (National Institute of Informatics). The primary outcomes will be the resumption of menstruation and the serum FSH levels, and the secondary outcomes include the serum Estradiol levels, anti-Mullerian hormone levels, antral follicle count, follicular growth, endometrial thickness, and adverse events. We will use RevMan V.5.3 to conduct the meta-analysis, if possible. If it is not allowed, a descriptive analysis or a subgroup analysis will be conducted. Risk ratio for dichotomous data and mean differences or standardized mean differences for continuous data will be calculated with 95% confidence intervals using a random effects model or a fixed effects model. RESULTS: This study will provide the latest analysis of the currently available evidence for the efficacy of acupuncture in treating POI. PROSPERO REGISTRATION NUMBER: CRD42019125996.